Estudio de Factibilidad para la creación de una Empresa Procesadora y Comercializadora de Caucho Reciclado Styrene - Butadiene Rubber en la Provincia de Loja - Rodríguez Cueva, José Rolando (2017)
This project aims to determine the feasibility of the creation of a "PROCESSING AND MARKETING COMPANY OF RECYCLED RUBBER STYRENE - BUTADIENE RUBBER IN THE PROVINCE OF LOJA", using different proposed studies of specific objectives such as: Market, administrative, Technical, financial and financial evaluation, which led to conclusions and recommendations, This project begins with a general introduction to the history of rubber, its recycling and its environmental impact, a reference framework on the product to be manufactured in the company, a conceptual framework, the methodology approach involving the deductive methods And inductive techniques used to achieve specific and general objectives. When conducting the market study, the population was determined to study and applying a census to the claimants and offerers, information was obtained that helped to establish key points such as: potential, real and effective demand, projected and unsatisfied demand, average consumption , The marketing mix which shows how the retail price was established based on competition, cost of production and profit margin. Afterwards, the technical study determines the exact location of the plant, the installed and used capacity, the machinery used in production and maintenance, the flow chart of the production process, and the physical distribution of the plant with its respective Areas and access routes in case of fire and for the movement of the finished product. Next, in the elaboration of the administrative study, the mission, vision, values, general and specific objectives of the company were carried out to direct it, as well as the structural and functional organization chart and the function manuals that delimited the activities of each one of them. The members of the company; And the legal part in 5 which the documents necessary for the correct operation of the company are determined. The following is a financial study whereby the different fixed assets, deferred and current assets, the amount of own and external capital, fixed and variable costs, revenues obtained from sales, and the statement of income and Know at the end of each accounting period what will be the financial reality of the company. Subsequently, a financial evaluation is made to know the annual cash flows, the cost-benefit ratio, the internal rate of return of the project, the period in which the capital is recovered, etc., a financial analysis is carried out with an increase of Costs and another with a decrease in income. As a culmination, conclusions are drawn such as: The growth of the automotive fleet in the province of Loja benefits from obtaining the raw material, multiple applications of the product in: urban real estate, parking stops, speed breaks, etc .; Advantages of asphalt with adherence of rubber particles in relation to normal asphalt in relation to durability; Reduction of environmental pollution, among others. And recommendations such as: For the execution of this project or any other it is necessary to carry out studies of: market, technical, administrative, financial a financial evaluation, research methods and techniques; The legal requirements must be analyzed and executed with complete accuracy to ensure the proper functioning of the company, etc. Among other